Strategi Pengembangan Kecerdasan Emosional Santri di Yayasan Pondok Pesantren Attohiriyah Alfadiliyah Bodak Lombok Tengah - Abdurrahman Abdurrahman; Syamsul Arifin; Mohammad Fakhri; Zihniatul Ulya (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2023)
Learning strategies can be interpreted as plans which contain a series of activities designed to achieve certain educational goals. The strategies referred to this research are about the ways carried out by parties who have a relationship with the development of the students’ emotional quotient, with those strategies it is hoped that the students’ emotional quotient can develop easily without having to sacrifice big things. The objectives of this research were to find out how the strategies for developing the students’ emotional quotient were, and how the quality of emotional quotient was developed at the Foundation of Attohiriyah Alfadiliyah Islamic Boarding School in Bodak, Central Lombok. This type of research was descriptive qualitative research. Techniques used in collecting the data were observation, semi-structured interviews, and documentation. The researcher used data condensation, data presentation, and conclusion drawing in doing data analysis. The results of the research showed that the strategies used in developing the students’ emotional quotient were in the form of (1) studying the book of Ta'lim Muta'allim and the book of Al-Akhlak Lil Banin, (2) Avoiding excessive criticism, avoiding derogatory comments, or making fun of children, (3) Using visitation and praise to train children, (4) Teaching to be honest, (5) Getting used to or managing emotions. Furthermore, the quality of the male students’ emotional quotient at the Foundation of Attohiriyah Alfadiliyah Islamic Boarding School in Bodak, Central Lombok, was on average in managing anger and love feeling was relatively very good.